Identification of Essential Genes Associated With Prodigiosin Production in Serratia marcescens FZSF02 - Jia, Xianbo; Liu, Fangchen; Zhao, Ke; Lin, Junjie; Fang, Yu; Cai, Shouping; Lin, Chenqiang; Zhang, Hui; Chen, Longjun; Chen, Jichen (Frontiers in Microbiology, 2021)
Prodigiosin is a promising secondary metabolite produced mainly by Serratia strains. To study the global regulatory mechanism of prodigiosin biosynthesis, a mutagenesis library containing 23,000 mutant clones was constructed with the EZ-Tn5 transposon, and 114 clones in the library showed an altered prodigiosin production ability. For 37 of the 114 clones, transposon insertion occurred on the prodigiosin biosynthetic cluster genes; transposon inserted genes of the 77 clones belonged to 33 different out side prodigiosin biosynthetic cluster genes. These 33 genes can be divided into transcription-regulating genes, membrane protein-encoding genes and metabolism enzyme-encoding genes. Most of the genes were newly reported to be involved in prodigiosin production. Transcriptional levels of the pigA gene were significantly downregulated in 22 mutants with different inserted genes, which was in accordance with the phenotype of decreased prodigiosin production. Functional confirmation of the mutant genes involved in the pyrimidine nucleotide biosynthesis pathway was carried out by adding orotate and uridylate (UMP) into the medium. Gene complementation confirmed the regulatory function of the EnvZ/OmpR two-component regulatory system genes envZ and ompR in prodigiosin production.